The Effectiveness of Four-Wheel Patrol Utilizing Whatsapp for Preventing Motorcycle Theft at Pabuaran Police Sector in Cirebon Police Resort - Harold Sitorus, Grant (Proceedings of Police Academy, 2024)
This study aims to analyze the effectiveness of four-wheeled patrols utilizing WhatsApp in preventing motorcycle theft (curanmor) within the jurisdiction of the Pabuaran Police Sector, Polresta Cirebon. The research employs a qualitative method with data collection techniques including participatory observation, structured and unstructured interviews, and document analysis. The findings indicate that WhatsApp-based patrols contribute to enhanced supervision but remain partially effective due to various challenges. The primary obstacles include a limited number of personnel, suboptimal use of technology, and low public awareness regarding vehicle security. This study suggests improving supervision, optimizing digital technology, and educating the public to support patrol effectiveness and foster a safer environment in the Pabuaran Police Sector area.